2020
DOI: 10.1080/17425247.2021.1823964
|View full text |Cite
|
Sign up to set email alerts
|

Emerging skin-targeted drug delivery strategies to engineer immunity: A focus on infectious diseases

Abstract: Introduction: Infectious pathogens are global disrupters. Progress in biomedical science and technology has expanded the public health arsenal against infectious diseases. Specifically, vaccination has reduced the burden of infectious pathogens. Engineering systemic immunity by harnessing the cutaneous immune network has been particularly attractive since the skin is an easily accessible immuneresponsive organ. Recent advances in skin-targeted drug delivery strategies have enabled safe, patientfriendly, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 267 publications
(272 reference statements)
1
15
0
Order By: Relevance
“…Although the role of skin as a protective physical barrier has been broadly recognized, its unique ability to serve as an immune-responsive organ has more recently been appreciated due to advances in our understanding of skin immune mechanisms that initiate and regulate innate and adaptive immune responses against invading pathogens [ [89] , [90] , [91] , [92] ]. Emerging knowledge has revealed that there is both a high density of professional antigen-presenting cells (APCs) and immune-accessory cells that form a tightly regulated immune network within the skin microenvironment [ 42 , [91] , [92] , [93] , [94] , [95] , [96] ]. Our increasing understanding of the mechanisms underlying immune regulation in the skin provides novel opportunities to rationally develop effective skin-targeted vaccines based on localized immune engineering.…”
Section: The Skin As An Immune-responsive Organmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the role of skin as a protective physical barrier has been broadly recognized, its unique ability to serve as an immune-responsive organ has more recently been appreciated due to advances in our understanding of skin immune mechanisms that initiate and regulate innate and adaptive immune responses against invading pathogens [ [89] , [90] , [91] , [92] ]. Emerging knowledge has revealed that there is both a high density of professional antigen-presenting cells (APCs) and immune-accessory cells that form a tightly regulated immune network within the skin microenvironment [ 42 , [91] , [92] , [93] , [94] , [95] , [96] ]. Our increasing understanding of the mechanisms underlying immune regulation in the skin provides novel opportunities to rationally develop effective skin-targeted vaccines based on localized immune engineering.…”
Section: The Skin As An Immune-responsive Organmentioning
confidence: 99%
“…Microarray patches (MAPs) are among the most promising skin-targeted vaccine delivery systems [ 42 , 44 , 202 ]. One of the major roadblocks to the success of intracutaneous immunization has been the lack of safe, effective, convenient, patient-friendly, and inexpensive delivery technologies that can reliably administer vaccines to targeted skin microenvironments [ 167 , 170 , 203 ].…”
Section: Microarray Patchesmentioning
confidence: 99%
See 3 more Smart Citations